“I haven’t seen any results yet”: on ethical collaborative research in linguistics and the need for a standard protocol - Schifano Norma; Allen Patrick; Nellan Pascalina; Garcés Tomás Restrepo; Kasstan Jonathan R. (Linguistics)
What does ‘good’ ethical conduct in linguistics look like from the perspective of the communities with whom we work? We address this question by drawing on observations from a community-bridging and knowledge exchange exercise involving both researchers and members of researched communities. Based on the experiences of those co-authors on the research team working with and for two associations representing Latin Americans and Chagossians in the United Kingdom, we discuss power asymmetries in collaboration, academic gatekeeping, and issues surrounding knowledge production, with specific reference to the design and implementation of funded research projects in formal linguistics. The paper’s originality lies in the practical recommendations made to the formal linguistics community on the basis of our synthesis of the testimony offered, so as to promote equitable and ethical research conduct. These include a prioritising of principles drawn from community-based and participatory research frameworks, the co-design of a long-term action plan, and a reconsideration of resource allocation to incorporate opportunities for professional development and infrastructure building. Our contention is that striving for a research design that is beneficial to the community on their terms should be the guiding star of project planning inasmuch as it is both ethically compelling and achievable.